L’entretien collectif en contexte - Olivier Tschannen (Communication)
Researchers using focus groups should take into account the imbrication, within the interview process itself, of « internal » with « external » agencies. Although initially extrinsic to the interaction, these agencies can be analyzed provided that the interviewees interject them as part of the strategy they deploy during the interview.